Distribution of Midbrain Cholinergic Axons in the Thalamus - (:unkn) unknown (SOC NEUROSCIENCE, 2020)
Cholinergic transmission is essential for adaptive behavior and has been suggested to play a central role in the modulation of brain states by means of the modulation of thalamic neurons. Midbrain cholinergic neurons from the pedunculopontine nucleus (PPN) and the laterodorsal tegmental nucleus (LDT) provide dense innervation of the thalamus, but a detailed connectivity mapping is missing. Using conditional tracing of midbrain cholinergic axons in the rat, together with a detailed segmentation of thalamic structures, we show that projections arising in PPN and LDT are topographically organized along the entire extent of the thalamus. PPN cholinergic neurons preferentially innervate thalamic relay structures, whereas LDT cholinergic neurons preferentially target thalamic limbic nuclei. Moreover, both PPN and LDT provide a dense innervation of the intralaminar thalamic nuclei. Notably, we observe a differential synaptic density that functionally dissociates between PPN and LDT innervation. Our results show that midbrain cholinergic neurons innervate virtually all thalamic structures and this innervation is functionally segregated.
Keywords: cholinergic innervation; conditional tracing; laterodorsal tegmental nucleus; pedunculopontine nucleus; LATERODORSAL TEGMENTAL NUCLEUS; BRAIN-STEM CORE; NONCHOLINERGIC NEURONS; MEDIODORSAL THALAMUS; PARAVENTRICULAR NUCLEUS; PROJECTIONS; INNERVATION; INTRALAMINAR; ORGANIZATION; FOREBRAIN